Table of Content - -, (Journal of Economic, Administrative and Legal Sciences, 2023)
Table of Content:1. Factors affecting the shadow economy and their impact on economic growth in the Kingdom of Saudi Arabia during the period (2007-2021)Dr. Vivian Mohammed saleh Nasrulddin, Mrs. Hessa saad Alshahrani2. The Impact of the Government Role in the Development of Small and Medium Enterprises in the Arab Republic of Egypt (Applying to Damietta Governorate)Dr. Ehab Mohamed Afifi, Prof. Mohamed Najib Abdel-Fattah , Dr. Iman Mustafa Muslim3. The effect of job satisfaction on the level of productivity among government health sector nurses in Riyadh A study of its application to Al-Iman General Hospital in RiyadhMr. Saleh Mohammed Al-Zoghaibi4. The Right of The Individual to The Safety of His physical and Psychological Being During the Investigation in Accordance with International Conventions and Islamic Law (Comparative Study)Dr. Abdelgadir Abdelrhman-Abdelgadir5. Judicial jurisprudence issued by Sharia courts in family reformDr. Waleed Khaled Baklizi6. Impact of Accounting Conservatism on Improving and  Evaluating The efficiency of the financial performance of Islamic banks (An analytical study on Faisal Islamic Bank during 2011 - 2015)Prof. Huda Diayb Ahmed, Dr. Randa Abdelhamied Mohammed, Dr. Badralden Mohammed Yhaya7. Critical Success Factors of Business Intelligence System in OrganizationsEng. Talha Abed-Al-Fattah Mashayekh , Dr. Hashem Mohammed Al-Aidaros , Dr. Haitham Zaker Khoj8. Protecting Child Refugees from Violence: Between Legal Texts and Practical ExperiencesCo-Prof. Maya Hasan Khater9. The application of the quick response manufacturing system (QRM) in Sudanese industrial companies and its impact on reducing costs and achieving competitive advantage (For the period 2017-2022) (Analytical study)Dr. Amira Abdalrhman Almekki
Keywords: Journal of Economic, Administrative and Legal Sciences